2018
DOI: 10.31803/tg-20180201002943
|View full text |Cite
|
Sign up to set email alerts
|

Low Power Steam Turbine Energy Efficiency and Losses During the Developed Power Variation

Abstract: This paper investigates low power marine steam turbine during the variation in its developed power. The turbine is used for the Main Feedwater Pump (MFP) drive. Energy analysis of the Main Feedwater Pump Turbine (MFPT) is based on the measurements performed in nine different operating regimes. The measured operating parameters were steam pressure and temperature at the turbine inlet, steam pressure at the turbine outlet, and a water volume flow through MFP. Turbine energy power losses are most influenced by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Investigations of turbogenerators [17] and similar low power steam turbines [18] during the change in developed power showed that this kind of steam turbines reaches its highest efficiencies at approximately 70 % -80 % of maximum load. Main feed water pump turbine usually consists of one Curtis stage [19] and is used for Main Feed water Pump (MFP) drive.…”
Section: Description and Operating Characteristics Of Marine Steam Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of turbogenerators [17] and similar low power steam turbines [18] during the change in developed power showed that this kind of steam turbines reaches its highest efficiencies at approximately 70 % -80 % of maximum load. Main feed water pump turbine usually consists of one Curtis stage [19] and is used for Main Feed water Pump (MFP) drive.…”
Section: Description and Operating Characteristics Of Marine Steam Prmentioning
confidence: 99%
“…3. -Main turbine real (polytropic) power: (18) -Main turbine ideal (isentropic) power: (19) -Main turbine energy loss: (20) -Main turbine energy efficiency: (21) -Main turbine energy power loss and real developed power ratio: (22) Steam specific enthalpies (h) and steam specific entropies (s) of the main propulsion turbine and both of its cylinders are calculated from measured steam temperatures and pressures at each operating point, Fig. 2, by using NIST REFPROP 9.0 software [41].…”
Section: Equations and Principles Of Marine Main Propulsion Steam Turmentioning
confidence: 99%
“…The first law of thermodynamics defines the energy analysis of any control volume or system [28,29]. In a steady state, while disregarding potential and kinetic energy, for a standard control volume can be defined mass and energy balance equations, according to [30,31]:…”
Section: Equations For the Calculation Of Energy Loss Through Gland Smentioning
confidence: 99%
“…Energy analysis of any system or control volume is related to the conservation of energy [29]. Mass and energy balance equations for a control volume in steady state can be expressed according to [30] and [31] by equations:…”
Section: Energy and Exergy Analysis Of Any Control Volumementioning
confidence: 99%